2009
DOI: 10.1117/1.3078803
|View full text |Cite
|
Sign up to set email alerts
|

Cancer photothermal therapy in the near-infrared region by using single-walled carbon nanotubes

Abstract: Single-walled carbon nanotubes (SWNTs) have a high optical absorbance in the near-infrared (NIR) region. In this special optical window, biological systems are known to be highly transparent. The optical properties of SWNTs provide an opportunity for selective photothermal therapy for cancer treatment. Specifically, CoMoCAT® nanotubes with a uniform size (about 0.81 nm) and a narrow absorption peak at 980 nm are ideal candidates for such a novel approach. Here, CoMoCAT® SWNTs are conjugated to folate, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
198
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(201 citation statements)
references
References 31 publications
2
198
0
1
Order By: Relevance
“…120 This unique property of CNTs has been exploited as a method for killing cancer cells via thermal effects. [121][122][123][124][125][126][127][128][129][130][131][132][133][134] The optical coupling of light with CNTs can be enhanced by the surface defects of CNTs based on the antenna theory, and nanotechnology induces intentional surface defects to increase nanotube heating. 122 This electrophysical characteristic of the engineered CNTs including boron and nitrogen dopants (p-type dopants) to improve the thermal destruction performance of tumor cells.…”
Section: Ptt For Cancer Treatmentmentioning
confidence: 99%
“…120 This unique property of CNTs has been exploited as a method for killing cancer cells via thermal effects. [121][122][123][124][125][126][127][128][129][130][131][132][133][134] The optical coupling of light with CNTs can be enhanced by the surface defects of CNTs based on the antenna theory, and nanotechnology induces intentional surface defects to increase nanotube heating. 122 This electrophysical characteristic of the engineered CNTs including boron and nitrogen dopants (p-type dopants) to improve the thermal destruction performance of tumor cells.…”
Section: Ptt For Cancer Treatmentmentioning
confidence: 99%
“…They suggested that if the SWNTs can be selectively internalized into cancer cells with specific tumor markers, NIR irradiation of the SWNT can selectively trigger thermal cell death without harming normal cells. Zhou et al 6 prepared the conjugate of the SWNTs and folate moiety, which selectively internalized the SWNT inside cells labeled with folate receptor tumor markers. The SWNT-folate conjugate enhanced the photothermal destruction of tumor cells (EMT6, mammary tumor cell) by a 980-nm NIR laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…This exothermic generation potential by NIR irradiation can be used for hyperthermia cancer therapy. [4][5][6][7] Kam et al 8 prepared a water-soluble single-walled carbon nanotube (SWNT) by conjugation of the SWNTs and single-stranded DNA, and functionalized by polyethyleneglycol with the target ligand including folic acid as the tumor marker. They showed that the SWNT can be selectively internalized into cancer cells with very specific tumor markers and that NIR irradiation of the SWNTs can trigger thermal cell death without damage to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies involving SWNTs or other nanoparticles-assisted photothermal treatment were based on high laser power density of 1-40 W/cm 2 [23][24][25][26][27][28]. However, high laser power density could cause non-selective photothermal damage to the surrounding normal tissues.…”
Section: Introductionmentioning
confidence: 99%